The knowledge of dentists for preventive influence of the caries process - Dobrinka Mitkova Damyanova; Valentina Velikova (Intelektual Pustaka Media Utama, 2020)
The line of knowledge runs from the general social, legal, financial and managerial framework. It is necessary to present the object of professional activity, the peculiarities of professional work and the methods for its optimization. Subjects of the survey were 100 dentists who perform treatment of deciduous teeth from the city of Varna, Bulgaria. The individual addressed anonymous survey was fulfilled during educational, clinical and organization meetings at the Faculty of Dental Medicine-Varna and on the territory of the city of Varna. The interviewed dentists encounter difficulties with the diagnosis of the initial dental caries in primary dentition. The dentists included in the survey rely mainly on their theoretical and practical experience and routine clinical methods for non-invasive treatment of the initial dental caries. Work experience and the specialty do not have a significant impact on the awareness of dentists about the new criteria related to the diagnosis and prevention of dental caries in the primary dentition. The age, work experience and specialty of dentists are factors for their awareness of the new approaches to treatment of children, as doctors up to 30 years of age, with a recognized specialty and work experience up to five years are more informed.